2012
DOI: 10.1002/jssc.201200131
|View full text |Cite
|
Sign up to set email alerts
|

Ultra performance liquid chromatography coupled with electrospray and atmospheric pressure chemical ionization (ESCi)‐quadrupole time‐of‐flight mass spectrometry with novel mass spectrometryElevated Energy (MSE) data collection technique: Determination and pharmacokinetics, tissue distribution and biliary excretion study of ergone in rat

Abstract: Ergosta-4,6,8(14),22-tetraen-3-one (ergone) has been proved to have novel antitumor effects on HepG2 cells. The aim of this study was to investigate the pharmacokinetics, tissue distribution, and biliary excretion of ergone in rats following a single oral administration (5, 10, and 20 mg/kg). The levels of ergone in plasma, tissues, and bile were measured by ultra performance liquid chromatography coupled with electrospray and atmospheric pressure chemical ionization (ESCi)-quadrupole time-of-flight mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Our previous study demonstrated that ergone could prevent progression of renal injury and subsequent renal fibrosis [21] . Pharmacokinetic studies indicated ergone was mainly excreted into the rat feces via bile instead of urine with approximately 57% of the loading dose present in the feces within 24 h [22] [25] . Although therapeutic efficacy of ergone for CKD was demonstrated, the biochemical mechanism of its action was still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that ergone could prevent progression of renal injury and subsequent renal fibrosis [21] . Pharmacokinetic studies indicated ergone was mainly excreted into the rat feces via bile instead of urine with approximately 57% of the loading dose present in the feces within 24 h [22] [25] . Although therapeutic efficacy of ergone for CKD was demonstrated, the biochemical mechanism of its action was still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The following pharmacokinetic parameters were measured after a single oral administration (20 mg/kg) of ergone to rats: the area under the plasma concentration versus time curve from time 0 h to indefinite time (AUC 0–∞ ) was 19.6 μg h mL −1 , peak plasma concentration (C max ) was 1.5 μg/mL, the elimination half-life (t 1/2 ) was 5.90 h, and time to C max (T max ) was 3.8 h [ 266 ].…”
Section: Ketonesmentioning
confidence: 99%
“…In general, the UPLC technique is combined with high‐resolution mass spectrometry (HRMS) for metabolite identification in vitro or in vivo . Quadrupole time‐of‐flight mass spectrometry (QTOF‐MS), a HRMS technique, allows the generation of mass information with higher accuracy and precision for the identification of known or unknown compounds, which could provide candidate empirical formulae with a mass error of less than 5 ppm . Accordingly, the Waters QTOF mass spectrometer was able to generate accurate mass data which could be used to calculate elemental compositions of metabolites or their fragment ions .…”
mentioning
confidence: 99%